Sengkalan Memet Pada Cagar Budaya Cirebon - Agus Dody Purnomo; Ardianto Nugroho; Anggoro Cipto Ismoyo (JURNAL RUPA, 2020)
In Javanese culture, a symbol has become a common media to describe historical events. One of the symbols used to describe it is Sengkalan Memet. Sengkalan Memet consists of three elements, visual, Sengkalan sentences, and the number of years of important events happening. Sengkalan Memet consists of pictures configuration, statue, or even a building. Keraton Kasepuhan Cirebon dan Taman Sunyaragi is one of the cultural heritage places that have Sengkalan Memet. The study is to explore Sengkalan Memet and the meaning in the Keraton Kasepuhan Cirebon and Taman Sunyaragi. The methodology implemented in this study is using a descriptive qualitative method. This study is expected to be an added value for artists, architects, designers and creative industries to take advantage of local wisdom. Furthermore this study can be used as an approach for design in this global era.